ANALYSIS OF THE POSTAL MARKET IN SLOVAKIA AND SELECTED COUNTRIES - Madlenakova, Lucia (Doprava a spoje, 2006)
Postal services provide vital infrastructural support for the commercial, governmental, intellectual, social and financial activities of the country. In this period, many of the universal service providers have an important role in these markets. But the public services have a central role in an effective and dynamic dingle market. Providing high quality services of general interest to all citizens at affordable prices is also necessary. These efforts are all the more important as the image of the traditional postal services I now changing. Postal services providers have evolved into complex modern industrial organizations, benefiting from technology developments that create new opportunities for more innovative, tailors, value added services in the interest of both commercial customers and end consumers and remove barriers to competition in the postal sector.